Training: An Effective Tool for Transfer of Agricultural Technologies - Jaiswal, Monika; Singh, Ajeet; Singh, Kartikey; Singh, Bhupendra (Indian Journal of Extension Education, 2021)
Training of farmers and farm women has always been regarded as critical input for the rapid transfer of technologies. The present study was carried in five adopted villages of Krishi Vigyan Kendra, Burhanpur during 2014-15 to 2018-19. Out of over 100 different training programmes organized on various topics like pre sowing techniques, crop management practices, post-harvest management, goatery production and livestock management practices by KVK, Burhanpur during last five years a sample of 500 adult members actively participated in the training programmes was selected. The study revealed that the on campus training was most preferred by majority of the farmers, followed by off campus training programme. The farmers rated one to three days duration training organized during lean period as most preferred training programme for farmers.